Tales from Earthsea - Le Guin, Ursula K., 1929-2018. (New York : Harcourt, 2001)
Explores further the magical world of Earthsea through five tales of events which occur before or after the time of the original novels, as well as an essay on the people, languages, history and magic of the place.
The finder -- Darkrose and Diamond -- The bones of the earth -- On the high marsh -- Dragonfly -- A description of Earthsea.
Keywords: Fantasy fiction, American; Fantasy; Short stories